Description of the female Apocolotois smirnovi (Romanoff, 1885) (Lepidoptera: Geometridae, Ennominae), with comments on the biology and distribution of the species - Japaridze, Lasha-Giorgi; Malkiewicz, Adam; Sanakoeva, Alisa; Tsulaia, Mariam; Bulbulashvili, Natalia; Õunap, Erki (Zootaxa, 2021)
The hitherto unknown female of Apocolotois smirnovi (Romanoff, 1885) is described based on two specimens from Tbilisi, Georgia. To date, only males of this rare Transcaucasian species were known. The results of DNA barcoding are presented, larva and pupa of A. smirnovi are figured, and the biology and distribution of the species are commented on.